Subjective Memory Complaints and Decision Making in Young and Older Adults: An Event-Related Potential Study - Garrido-Chaves, Ruth; Perez, Vanesa; Perez-Alarcón, Mario; Crespo-Sanmiguel, Isabel; Paiva, Tiago O.; Hidalgo, Vanesa; Pulopulos, Matias M.; Salvador, Alicia (Frontiers in Aging Neuroscience, 2021)
Subjective memory complaints (SMCs) may affect decision-making processes. This study aimed to investigate the neuronal correlates of feedback processing during a decision-making task in young and older adults with and without SMCs. Event-related potentials and behavioral performance during the Iowa Gambling task were recorded in a total of 136 participants (65 young adults, 71 older adults). The participants were divided into two groups according to their SMCs (with SMCs: n=60, without SMCs: n=76). Feedback-related negativity (FRN) and P3 were analyzed in the feedback stage of the decision-making process. Older adults with SMCs scored worse in the ambiguity phase than older adults without SMCs. The FRN latency was longer for losses in older people with SMCs than in older people without SMCs in the first block. No significant differences between young and older adults with and without SMCs were observed in the other ERP measures. Compared to young adults, older adults showed delayed latency in the FRN component and reduced amplitudes and delayed latency in the P3 component. SMCs are related to deficits in decision-making performance in older individuals, but not in younger adults. However, these differences are not reflected in neural correlates of feedback processing. Deficits in the decision-making process in older people with SMCs are not reflected in neural correlates of feedback processing.